Effects of Land Use/Cover Change on the Ecosystem Service Values in the Greater Bay Area of China Accounting for Spatiotemporal Complexity - Yingying Liu; Yalan Shi; Chunyu Liu (Complexity)
With the rapid development of the economy, the land use/cover change (LUCC) in the Greater Bay Area (GBA) has undergone tremendous changes, which have had directly negative effects on ecosystem functions and services. The development of sustainable land use strategies to quantitatively evaluate ecosystem services is required. Based on multitemporal land use data (2005, 2010, 2015, and 2020), the equivalent coefficients table method was used to assess the ecosystem service values (ESVs), and the impact of LUCC on ecosystem services was analyzed. A future land use simulation (FLUS) model and multiscenario simulations were employed to predict land use change in 2030. Our results indicated that the loss of ESVs decreased by 14.29 billion yuan from 2005 to 2020. The spatial distribution of the high-value ecosystem services was concentrated around the peripheral area of the northern regions in the GBA, and those areas had less land use development and human activity. Compared with those in 2020, the total ESVs of the business-as-usual (BAU) scenario, socioeconomic development (SED) scenario, and cultivated protection priority (CPP) scenario in 2030 decreased, while they increased in the ecological protection priority (EPP) scenario. In the CPP scenario, regulating, supporting, provisioning, and cultural services increased slightly, but they decreased in the other scenarios. The patterns of LUCC were the main reasons for the decrease in ESVs, such as the loss of land with high ecological value. Additionally, a four-quadrant analysis is introduced to determine which land use simulation will be expected to be adopted by the government. The findings of this study provide valuable information for decision-making and policy development in the coastal zones and for the sustainable management of ecosystems.